The Association Between Moderate and Vigorous Physical Activity and Time to Medical Clearance to Return to Play Following Sport-Related Concussion in Youth Ice Hockey Players - Lishchynsky, Justin T.; Rutschmann, Trevor D.; Toomey, Clodagh M.; Palacios-Derflingher, Luz; Yeates, Keith O.; Emery, Carolyn A.; Schneider, Kathryn J. (Frontiers in Neurology, 2019)
Design: Prospective cohort study. Background: The recommendations regarding the optimal amount and type of rest for promoting recovery following concussion are based on expert opinion rather than evidence-based guidelines due to current a lack of high-level studies. There is an evident need for more research into the parameters of rest and activity and its effects on recovery from concussion. Objective: To evaluate the association between the amount of moderate and vigorous physical activity (MVPA) during the first three days following concussion diagnosis and time to medical clearance (days) to return to play in youth ice hockey players. Methods: Thirty youth ice hockey players (12-17 years) that were diagnosed with a concussion sustained during ice hockey were recruited to participate. The exposure was the cumulative amount of MVPA (minutes), measured using a waist-worn Actigraph accelerometer. Participants were dichotomized into high (≥148.5) and low (<148.5) activity groups based on the median of cumulative time spent in MVPA over the first three days following injury diagnosis. Results: Participants in both the low and high activity group reported to the clinic at a median time of 4 days post-injury (low activity IQR: 3-5 days; high activity IQR: 3-7 days). The low activity group completed a median time of 110.7 minutes (IQR: 76.2-131.0 minutes) in MVPA, whereas the high activity had a median of 217.2 minutes (IQR 184.2-265.2 minutes) in MVPA. Kaplan Meier survival curves with Log-rank tests of hypothesis revealed the high activity group took significantly more time to be medically cleared to return to play (p=0.041) compared to the low activity group. Conclusion: The results from this study suggest that more time in MVPA early in the recovery period may result in a greater time to medical clearance to return to full participation in ice hockey. Future research, using valid measures of activity, are required to better understand the relationship between early activity and recovery following concussion in youth. Word Count: 318